2023
DOI: 10.3847/2041-8213/acd77b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of X-Ray Polarized Emission and Accretion-disk Winds with IXPE and NICER in the Black Hole X-Ray Binary 4U 1630−47

Abstract: We detect a high level of polarization in the X-ray emission of the black hole binary 4U 1630–47 in an observation with the Imaging X-ray Polarimetry Explorer. The 2–8 keV polarization degree is 8% at a position angle of 18°, with the polarization degree increasing significantly with energy, from ∼6% at ∼2 keV to ∼11% at ∼8 keV. The continuum emission in the spectrum of simultaneous observations with the Neutron Star Interior Composition Explorer (NICER) is well described with only a thermal disk spectrum, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Two other works have independently analyzed the same IXPE data sets (Kushwaha et al 2023;Rawat et al 2023), obtaining observational results consistent with those presented in this work. The authors posit that the high PD can be explained by scattering off a wind.…”
Section: Discussionsupporting
confidence: 83%
“…Two other works have independently analyzed the same IXPE data sets (Kushwaha et al 2023;Rawat et al 2023), obtaining observational results consistent with those presented in this work. The authors posit that the high PD can be explained by scattering off a wind.…”
Section: Discussionsupporting
confidence: 83%
“…In light of this, the launch of the IXPE mission provides an opportunity to investigate the evolution of spectral transitions through X-ray polarimetry and probe the corona geometry . Previously , Rawat et al ( 2023 ), Kushwaha et al ( 2023 ), andRatheesh et al ( 2023 ) reported a significant polarization of 8 per cent for 4U 1630 in the HSS with IXPE . Similarly, Podgorny et al ( 2023 ) and Dovciak et al ( 2023 ) hav e observ ed polarization fraction of ∼1.1 per cent for LMC X-1 and ∼2.27 per cent for Cygnus X-1 in the HSS and the variable soft state, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…4U 1630 −472 (hereafter 4U 1630) is a transient low-mass X-ray binary source disco v ered almost fiv e decades ago with Uhuru , Ariel V (Jones et al 1976 ), and Vela 5B X-ray monitor (Priedhorsky 1986 ), independently. This source shows particularly soft outbursts with a lack of hard X-ray emission (Capitanio et al 2015 ) and multiple iron absorption lines in the 6-9 keV band (Kubota et al 2007 ;R ó ża ńska et al 2014 ;Miller et al 2015 ;Rawat, Garg & M éndez 2023 ). There is a discrepancy in the measurement of the inclination angle of the source; Kuulkers et al ( 1998 ), and King et al ( 2014 ) reported it as E-mail: rawatdivya838@gmail.com a high-inclination source ( ∼60-70 • ), while R ó ża ńska et al ( 2014 ) proposed that it is a low-inclination system ( i ∼ (11 ± 5) • ).…”
Section: Introductionmentioning
confidence: 98%
“…4U 1630-47: IXPE had observed 4U 1630-47 from 23-Aug-2022 to 02-Sept-2022, when the source is in high soft spectral state. The polarisation properties have been analysed by three groups (Rawat et al 2023;Kushwaha et al 2023;Ratheesh et al 2023), and they found that PD is an energy-dependent which increases significantly with energy. In 2-8 keV band PD is ∼0.08 and PA in the sky plane is ∼18 • .…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…Sharma et al 2020;Chattopadhyay et al 2019;Chand et al 2019), by INTEGRAL/SPI (McGlynn et al 2007) /IBIS (G.tz et al 2014), by POLAR (Zhang et al 2019), by other instruments, for example, GAP (see in details Chattopadhyay et al 2019). Recently, IXPE has measured polarisation properties of many XRBs, AGNs, pulsar in 2-8 keV energy band (Weisskopf et al 2022;Rawat, Garg, & Méndez 2023;Marshall et al 2022;Jayasurya, Agrawal, & Chatterjee 2023;Pal et al 2023;Marinucci et al 2022;Doroshenko et al 2022), and for few sources the polarisation is an energydependent. Long et al (2022) quantified the polarised emission of Sco X-1 using PolarLight observations in 3-8 keV and noted an energy-dependent polarisation.…”
Section: Introductionmentioning
confidence: 99%